Penggunaan Aplikasi Tiktok Terhadap Pemenuhan Kebutuhan Informasi Bagi Kalangan Remaja Madrasah Tsanawiyah Bina Insani - Anggita, Rizki; Rozi, Fakhrur; Abidin, Syahrul (CV. ITTC INDONESIA, 2023)
This study aims to determine the use of the Tiktok application to fulfill information needs for teenagers at Madrasah Tsanawiyah Bina Insani. The theory used is uses and gratification and the research method uses quantitative. The results showed that the level of use of the Tik-Tok application to fulfill information needs among teenagers at Madrasah Tsanawiyah Bina Insani quite often used the Tiktok application, the majority of respondents used the Tik Tok application more than 10 times a day. Information needs through the Tik Tok application can also be seen from the interest of Madrasah Tsanawiyah teenagers to increase knowledge, get information, gain new experiences, and to increase insight and interact with new friends. Bina Insani Madrasah Tsanawiyah teenagers also get news related to events that occur in the surrounding environment through the Tik Tok application. In addition, Bina Insaniyah Madrasah Tsanawiyah teenagers also get solutions related to a problem in the Tiktok application so that they can fulfill their information needs, and Bina Insani Madrasah Tsawaniyah teenagers can find information that is entertaining or can help respondents relax themselves from the daily routine.